Radiological indicators of acute radiation disease (chernobyl experience) - Domina, E.A.; Nikolaev, V.G. (Reports of the National Academy of Sciences of Ukraine, 2021)
We have studied the specificities of radiological parameters depending on the degree of acute radiation disease before and after intensive detoxification therapy of 53 victims of the Chernobyl accident. They were treated in the clinic of the Kyiv Research X-ray Radiology and Oncology Institute of the Ministry of Health of Ukraine. The manifestation of primary injuries in patients did not always correspond to the severity of radiation pathology. In general, we have observed the delayed development of leukopenia and lymphopenia was observed as compared to the classical form of radiation disease. The specificity of blood cytopenia was the wavy nature of its course. Restoration of blood parameters at a critical moment was possible only due to the donor bone marrow, which temporarily assumed haematopoietic function. A characteristic feature of ultrastructural changes in the bone marrow under mixed irradiation (external and due to radionuclides) were dystrophy and destructive changes in the endothelium of the sinuses of the bone marrow. All patients underwent biological (cytogenetic) dosimetry. For the first time, an algorithm for determining the degree of radiation disease based on the optimal set of cytogenetic indicators of radiation damage of T-lymphocytes with the involvement of a model of multiple linear regression was proposed. A comparison of cytogenetic dosimetry data with clinical symptoms allowed us to draw objective conclusions about the differentiation of the severity of radiation disease within the time required for timely detoxification therapy of victims. The Chernobyl experience showed the following. In case of radiation incidents, it is advisable to conduct a comprehensive radiological study, which includes haematological and cytogenetic examination, as well as an analysis of quantitative and morphological parameters of the bone marrow in comparison with the clinical symptoms of irradiated persons.